Symmetry breaking for representations of rank one orthogonal groups - Kobayashi, Toshiyuki; Speh, Birgit (Memoirs of the American Mathematical Society, 2015)
We give a complete classification of intertwining operators ( We obtain closed formulae for the functional equations which the composition of the symmetry breaking operators with the Knapp–Stein intertwining operators of